RETRACTED: Lung Abnormalities in Liver Cirrhosis - Muli Yaman; Mustika, Syifa (Clinical and Research Journal in Internal Medicine, 2023)
Clinical and Research Journal in Internal Medicne has retracted article titled: "Lung Abnormalities in Liver Cirrhosis" by Muli Yaman, and Syifa Mustika, from Vol. 4, No. 2 (2023) since there has been similar publication found in Current Internal Medicine Research and Practice Surabaya Journal (CIMRJ) Vol. 4, No. 1 (January 2023).This retraction announcement is necessary to maintain publication ethics.